O ensino de ciências na educação básica, anos iniciais na comunidade escolar Quilombola Mesquita - Bomfim, Antonio Marcos (2024)
This study arose from the following question: how do teachers teach natural sciences in a traditional quilombola community to students in the early years of elementary school? In order to answer this question, the central objective was to analyze how the process of teaching Nature Sciences to children in the Mesquita Quilombola Community takes place. To this end, the following specific objectives were set: 1) to present the historicity and organization of quilombo in Brazil, from its initial formation to the present day, specifically arriving at the Mesquita Quilombo Remnant Community; 2) to examine in current literature how the Teaching of Natural Sciences occurs in a Quilombola School Community; 3) to verify in which aspects public policies on the teaching of Natural Sciences contribute to the integral formation of students from quilombola communities and finally the educational product, with the aim of putting the practice of scientific investigation in line with quilombola knowledge and highlighting the importance of this theme in the analysis of an emancipatory education as a curricular policy. The research is based on the writings of Quilombos - Resistance and Slavery by Clóvis Moura (1989); O Quilombismo - Documentos de uma Militância Pan-Africanista by Abdias Nascimento (2019); Uma História Feita por Mãos Negras by Beatriz Nascimento (2021); Mocambos e Quilombos - Uma História do Campesinato Negro no Brasil by Flavio dos Santos Gomes (2015); Quilombo Mesuita: history, culture and resistance by Manuel Barbosa Neres (2016); Popular Education by Carlos Rodrigues Brandão (1985); Labor and monopoly capital: the degradation of work in the 20th century by Harry Braverman (1987); Attico. A ciências através dos tempos by Attico Chassot (2011); Education as a Process of Political Struggle: The Experience of "Differentiated Education" in the Quilombola Territory of Conceição das Crioulas by Givânia Maria da Silva (2012); A terra Dá a Terra Quer by Antonio Bispo dos Santos (2022), among others, as well as legal documents dealing with the issue in question. This is a qualitative study, based on a case study. The first two specific objectives were developed through qualitative bibliographical research. The results of the research show that traditional quilombola knowledge is not incorporated into the educational practices of the school studied, as required by the guiding documents for Quilombola School Education in relation to the teaching of natural sciences.